PENGARUH SISTEM HUKUM PERLINDUNGAN MEREK YANG ADA DI INDONESIA DENGAN NILAI EKONOMI MEREK - Gufta Alvian Irsyada; Elfrida Ratnawati Gultom (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Trademark is a sign used in trade to differentiate goods and services on the market. Trademark have economic value which is indicated by how well the product with the trademark sells in the market. Trademark that sells well in the market have a good brand image. Trademark with a good brand image is prone to branding infringement practices therefore we need a legal system to protect the trademark form infringement practices. This makes the author interested in conducting research on the legal system that protects trademark and their effect on the economic value of trademark. The legal system that the writer wants to research is the legal system according to Friedman which consists of legal substance, legal structure and legal culture. The research method used by the author is a normative research method with secondary data. The secondary data are from primary legal sources, secondary legal sources and tertiary legal sources. The approach used is the statutory approach and the theoretical approach. Data is collected from literature study that will be used to describe the trademark protection legal system in Indonesia and its impact on the economic value of brands.Keywords: Economic value of trademark, Trademark Protection, Legal System.